POTENSI ZEOLIT ALAM MODIFIKASI PERAK DALAM MENGHAMBAT PERTUMBUHAN BAKTERI AGGREGATIBACTER ACTINOMYCETEMCOMITANS - Catur Septommy (Bhakta Dental Journal, 2023)
Background: Bacterial colonies involving A. actinomycetemcomitans will initiate inflammation in the gingiva and extend to periodontal tissues. Zeolite is a porous natural mineral that can be modified with several metals, metal ions in zeolite are able to enter the cytoplasm and increase the production of reactive oxygen species (ROS), causing cell death. The condition of antibiotic-resistant periodontitis patients can be treated with alternative therapies using metal-based materials. Research Objective: to determine the effect of silver solution concentration on zeolite on the growth inhibition of A. actinomycetemcomitans bacteria. Research Methods: Activation of zeolite with 500 ml of 3 M HCl solution for 12 hours. Ag-Zeolite modification by immersing 6 g of active zeolite in 60 ml of 0.025 M, 0.50M, and 0.1M AgNO3. Test the inhibition of modified zeolite on MHA media that has been swabbed with A. actinomycetemcomitans. Results: Zeolite modified 0.1M AgNO3 has the highest inhibition. Conclusion: The combination of silver on zeolite can affect the growth of A. actinomycetemcomitans bacteria.